2009
DOI: 10.4161/cam.3.1.7511
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin associated protein 1 and its functions

Abstract: Huntington disease (HD) is caused by a polyglutamine expansion in the protein huntingtin (Htt). Several studies suggest that Htt and huntingtin associated protein 1 (HAP1) participate in intracellular trafficking and that polyglutamine expansion affects vesicular transport. Understanding the function of HAP1 and its related proteins could help elucidate the pathogenesis of HD. The present review focuses on HAP1, which has proved to be involved in intracellular trafficking. Unlike huntingtin, which is expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 102 publications
(142 reference statements)
0
27
0
Order By: Relevance
“…In accordance with the expression changes of MT family members, zinc and copper had cyclic concentration changes in the endometrium. The zinc concentration in the endometrium was lowest in the late proliferative phase (cycle days 10 -12), and it gradually increased afterward and reached its highest level during the late secretory phase (cycle days [25][26][27]. The copper concentration in the endometrium was lowest around the expected time of ovulation (cycle days 14 -15) and highest in the midand late secretory endometrium (cycle days 20 -27) (31).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In accordance with the expression changes of MT family members, zinc and copper had cyclic concentration changes in the endometrium. The zinc concentration in the endometrium was lowest in the late proliferative phase (cycle days 10 -12), and it gradually increased afterward and reached its highest level during the late secretory phase (cycle days [25][26][27]. The copper concentration in the endometrium was lowest around the expected time of ovulation (cycle days 14 -15) and highest in the midand late secretory endometrium (cycle days 20 -27) (31).…”
Section: Discussionmentioning
confidence: 95%
“…In humans, ZCCHC12 has been reported to be a potential molecular marker for papillary thyroid carcinoma and a candidate X-linked mental retardation gene (26). HAP-1, the first protein shown to interact with huntingtin, is specifically expressed in human brain tissue and involved in Huntington disease pathogenesis (27). A previous study has shown that HAP-1 is involved in vesicular transport (28).…”
Section: Discussionmentioning
confidence: 98%
“…Hap1 is a cytoplasmic protein that interacts with huntingtin (Htt), a protein known to cause Huntington disease when there is increased polyglutamine expansion in Htt (16). HAP1 is also thought to be involved in the neuropathogenesis found in Huntington disease through its aberrant binding with mutant Htt (17,18), and may act as a modifier for Huntington disease onset (19). Unlike Htt, which is ubiquitously expressed, Hap1 is predominantly expressed in the CNS, especially in the hypothalamus, striatum, and brainstem; areas that are highly enriched in Ahi1 (10,14).…”
mentioning
confidence: 99%
“…Hap1 participates in the endocytosis of channel receptor and transport of different growth factors (Li and Li 2005; Wu and Zhou, 2009). The diverse functions of Ahi1/Hap1 in the transport of various proteins can be specified in particular types of cells or during specific periods of brain development, depending on their interacting proteins.…”
Section: Discussionmentioning
confidence: 99%